Strategic narratives in the system of mechanisms for countering informational influence - Snytko , Olena (Current issues of Ukrainian linguistics: theory and practice, 2020)
The study addresses the issue of strategic communications in Ukraine’s information space. It defines strategic communications as a system of informational multi-dimensional interaction with the public on socially relevant topics through diverse mass media outlets directed at promoting national goals. Strategic communications aim at exerting influence on the individual by appealing to the freedom of speech principle and providing strong encouragement towards independent decision-making, as well as by drawing the public’s attention to socially relevant issues and the ways to approach them. Strategic communications entail the emergence of distinct strategic narratives. Therefore, gaining a better insight into strategic narratives allows determining the causes of the socially significant situation and the prospects for its resolution. The paper explores the narrative about the origin of the Ukrainians, which is steadily unfolding in the information space. This narrative represents a distinct multimodal semantic plural aimed at promoting the idea of national identity and statehood. The study has found that different versions of the strategic narrative about the origin of the Ukrainians in the Internet space have similar semantic and conceptual patterns and involve multiple narrators. At the same time, they provide varying amounts of information and commenting features, target different audiences, and, for this reason, require relevant tools of influence, namely argumentation and suggestion. Тhe methods of randomizing ideas, breaking patterns, and creating cognitive dissonance are widely used in the creolized political texts. In the context of information warfare, a powerful strategic narrative, as a rule, instigates the emergence of a counter-narrative, which has an asymmetrical structure. The struggle of narratives has become the dominant feature of modern media space.
Keywords: strategic communications, strategic narrative, structure and variety of narrative, counter-narrative and its asymmetrical structure.